2011
DOI: 10.1209/0295-5075/93/28008
|View full text |Cite
|
Sign up to set email alerts
|

The role of interstitial gas in determining the impact response of granular beds

Abstract: Abstract. -We examine the impact of a solid sphere into a fine-grained granular bed. Using high-speed X-ray radiography we track both the motion of the sphere and local changes in the bed packing fraction. Varying the initial packing density as well as the ambient gas pressure, we find a complete reversal in the effect of interstitial gas on the impact response of the bed: The dynamic coupling between gas and grains allows for easier penetration in initially loose beds but impedes penetration in more densely p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 23 publications
10
48
0
Order By: Relevance
“…This interesting observation is consistent with the data in Figs. 3(a), 3(b), and 3(c) and also fits with previous conclusions regarding the initial packing state relative to the critical packing state [8,23].…”
Section: Irregular Grainssupporting
confidence: 89%
See 2 more Smart Citations
“…This interesting observation is consistent with the data in Figs. 3(a), 3(b), and 3(c) and also fits with previous conclusions regarding the initial packing state relative to the critical packing state [8,23].…”
Section: Irregular Grainssupporting
confidence: 89%
“…However, it is unclear how the rattlers affect the dynamical response of the granular material to impact, for example, or how they affect the interstitial forces between grains. Our study here indicates that the inclusion of fine grains into a bed of larger grains brings in the influence of ambient air and local fluidization, which has been observed previously for dense spheres impacting onto granular beds [23][24][25] and in falling granular streams [29,30]. The influence of ambient air only appears to be significant for finer grains (Geldart group A), such as the smallest particles used here with d p = 31 μm, and is typically not present for larger grains (Geldart group B, typically with mean diameter between 40 and 500 μm), such as the larger grains used here with d p = 178 and 520 μm, according to Geldart's classification [31].…”
Section: Effect Of Packing Fractionsupporting
confidence: 85%
See 1 more Smart Citation
“…The importance of the role of interstitial air in the formation of granular jets was established by high speed X-ray radiography and digital video imaging in [177,178]. These experiments report the presence of two jets when a projectile hits a bed of loosely packed sand: a thin, wispy jet whose size does not depend on the air pressure, and an air pressure-dependent thick jet.…”
Section: Granular Jets Granular Streams and The Segregation Of Vibramentioning
confidence: 99%
“…8 shows the emergence of granular jets following the impact of a projectile on a sand bed under two different air pressure conditions. The complex interplay between interstitial gas, bed particles and the impacting sphere has been studied in detail in [178,179]. Videos of granular jets can be viewed at [180] and a review on sand jets can be found in [181].…”
Section: Granular Jets Granular Streams and The Segregation Of Vibramentioning
confidence: 99%